1999
DOI: 10.1136/jnnp.67.1.113
|View full text |Cite
|
Sign up to set email alerts
|

Right frontal lobe slow frequency repetitive transcranial magnetic stimulation (SF r-TMS) is an effective treatment for depression: a case-control pilot study of safety and efficacy

Abstract: Major depression may result from decreased left frontal lobe function with respect to the right. Fast frequency repetitive transcranial magnetic stimulation (FF r-TMS) excites the underlying cortex whereas slow frequency repetitive transcranial magnetic stimulation (SF r-TMS) causes cortical inhibition. Left frontal FF r-TMS attenuates major depression whereas the inhibitory eVects of right frontal SF r-TMS are unknown. This study tested the hypothesis that right frontal SF r-TMS would treat depressed patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
39
0
8

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(48 citation statements)
references
References 15 publications
1
39
0
8
Order By: Relevance
“…Three patients had a pattern considered as remission, 15 with a punctuation below 8 in the same scale.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Three patients had a pattern considered as remission, 15 with a punctuation below 8 in the same scale.…”
Section: Resultsmentioning
confidence: 99%
“…In our study, we have initially used biweekly applications, as there were previous reports in the literature which had used this protocol. 15 As there was an improvement, we have chosen to augment it through the increase in the frequency of applications in future studies. This study was discontinued at this point precisely due to its positive results, which authorize and encourage us to use more frequent stimulations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Menkes et al 27 observed that there is a reduced activity of the frontal lobe, which results in impairment of planning activities in depressed individuals. However, the main point in the association of depression with motor performance appears to be in the deficiency of the neurotransmitter dopamine.…”
Section: Discussionmentioning
confidence: 99%
“…A estimulação de baixa frequência, por outro lado, diminui a atividade cerebral 9 . Menkes et al 10 sugeriram que a depressão maior deve ser o resultado de uma diminuição da função do lobo frontal esquerdo em relação ao direito. Baseados nesta hipótese, propuseram o tratamento com a estimulação magnética transcraniana de baixa frequência sobre o cór-tex frontal direito, com intuito de diminuir a atividade naquela área.…”
unclassified